Warianty poprawy efektywności energetycznej budynku szkolnego w Słubicach = Options to improve the energy efficiency of the building of a primary school in Słubice - Skiba, Marta; Rzeszowska, Natalia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Climate change and sustainable energy use is one of the five long-term objectives of the European Union. The first stage of the activities involving the implementation of this task is to reduce energy consumption of buildings to a minimum by 2020 and, in the case of public buildings by 2019.
Keywords: efektywność energetyczna; audyt energetyczny; szkoła; OZE; energy efficiency; energy audit; school; RES